Look at the Beat, Feel the Meter: Top–Down Effects of Meter Induction on Auditory and Visual Modalities - Celma-Miralles, Alexandre; de Menezes, Robert F.; Toro, Juan M. (Frontiers in Human Neuroscience, 2016)
Recent research has demonstrated top-down effects on meter induction in the auditory modality. However, little is known about these effects in the visual domain, especially without the involvement of motor acts such as tapping. In the present study, we aim to assess whether the projection of meter on auditory beats is also present in the visual domain. We asked sixteen musicians to internally project binary (i.e. a strong-weak pattern) and ternary (i.e. a strong-weak-weak pattern) meter onto separate, but analogue, visual and auditory isochronous stimuli. Participants were presented with sequences of tones or blinking circular shapes (i.e. flashes) at 2.4 Hz while their electrophysiological responses were recorded. A frequency analysis of the elicited steady-state evoked potentials allowed us to compare the frequencies of the beat (2.4 Hz), its first harmonic (4.8 Hz), the binary subharmonic (1.2 Hz), and ternary subharmonic (0.8 Hz) within and across modalities. Taking the amplitude spectra into account, we observed an enhancement of the amplitude at 0.8 Hz in the ternary condition for both modalities, suggesting meter induction across modalities. There was an interaction between modality and voltage at 2.4 and 4.8 Hz. Looking at the power spectra, we also observed significant differences from zero in the auditory, but not in the visual, binary condition at 1.2 Hz. These findings suggest that meter processing is modulated by top-down mechanisms that interact with our perception of rhythmic events and that such modulation can also be found in the visual domain. The reported cross-modal effects of meter may shed light on the origins of our timing mechanisms, partially developed in primates and allowing humans to synchronize across modalities accurately.